SURAT-SURAT SULTAN BUTON, DAYYAN ASRARUDDIN DAN KAIMUDDIN I, KOLEKSI UNIVERSITEITSBIBLIOTHEEK LEIDEN, BELANDA - . Suryadi (Humaniora, 2007)
SURAT-SURAT SULTAN BUTON, DAYYAN ASRARUDDIN DAN KAIMUDDIN I, KOLEKSI UNIVERSITEITSBIBLIOTHEEK LEIDEN, BELANDA).